Implementasi Metode Kriptografi dengan Menggunakan Algoritma RC4 dan Steganografi Least Significant Bit Dalam Mengamankan Data Berbasis Android (STMIK Budi Darma, 2022)
Security is a protection or protecting something important from something unwanted or other things that are theft of data security techniques, there are several ways to provide protection, one of which is by inserting something data that you want to protect into other media, message security. secret by inserting a message into an image file or better known as steganography is a development of a cryptography, where cryptography itself is a data security technique that contains elements of data management or formulation before it becomes new data and the new data can only be read or opened. by a certain person who can know the pattern of managing the data. The security and confidentiality of a message is very important and must be maintained, the problem of data confidentiality in a company or institution is a major problem where a lot of data that is confidential is open or widespread, this is very detrimental to the company, in addition to data confidentiality The other factor is that data confidentiality is a continued asset for the company to continue to managers in other divisions which must be maintained and used by someone appointed. From these problems, a cryptographic method is needed where the algorithm used is RC4 and steganography is used using Least Significant Bit (LSB) as the method. The advantage of RC4 is that the data in the management of making cryptography is more structured and has a non-static pattern in which the creation of confidential data can be made quickly and safely, while the Least Significant Bit (LSB) method is a method of inserting binary data into an image that has a color image and in it can accommodate 6 bits for the message. The purpose of this research is to create a cryptographic application system that combines the Least Significant Bit (LSB) technique to secure an android-based data